Retinol saturase in the mitochondria antagonizes IDH2 and GLUD1 acetylation to mediate heart repair - Wenya Ma; Yanan Tian; Jianglong Li; Qimeng Ouyang; Lei Xu; Bowei Zhang; Hongyang Chen; Hanjing Li; Yuqing Lin; Yu Hu; Zhongyu Ren; Yifu Shen; et al. (Proceedings of the National Academy of Sciences, 2026)
Facilitating endogenous cardiomyocyte proliferation has emerged as an important strategy for cardiac repair. Conserved retinol saturase (Retsat) functions in producing all-trans 13,14-dihydroretinol in the endoplasmic reticulum (ER). However, Retsat’s role and mechanism in heart regeneration remain unclear. Here, we uncover that Retsat is upregulated in cardiomyocytes during cardiac regeneration in mice. Cardiomyocyte-specific Retsat knockin promotes cardiac regeneration and improves cardiac function after injury. Conversely, cardiomyocyte-specific knockout of Retsat inhibits heart regeneration in neonatal mice. Surprisingly, Retsat drives cardiomyocyte proliferation independently of its classical retinol saturase activity in the ER. Retsat also localizes in cardiomyocyte mitochondria, and mitochondrial-specific overexpression of Retsat can stimulate cardiomyocyte proliferation and heart repair after injury. Mechanistically, Retsat in the mitochondria acts as an antagonist of Idh2 and Glud1 acetylation, reducing their acetylation levels and enhancing their activities. Furthermore, Retsat enters mitochondria by interacting with Tom70 and Tim23 proteins. These data suggest that targeting Retsat is a promising strategy for promoting cardiac regeneration after heart injury.